HUBUNGAN KECERDASAN EMOSIONAL DAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS X SMA NEGERI 1 PONTIANAK - Fikri, Khoirul; Yani T, Ahmad; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe The ability to think critically and the emotional intelligence of students is a matter of concern in the learning of mathematics. The importance of critical mathematical thinking ability are listed in the NCTM's objectives. This reseach aimed to know the correlation among emotional intelligence and mathematical critical thinking ability of the tenth grade students of SMA1 Pontianak. The method that used un this reseach was a quatitative descriptive with Ex Post Facto form. The subject of this research were second eleventh grade science that consist of 33 students. Data collection techniques in this research was a measurement technique in the form of essay and the scale of emotional intelligence. Based on the Kendall’s Tau test with significance level α = 5% found that there was a positive relationship between the students emotional intelligence and mathematical critical thinking ability with the correlation 0,435. So it can be concluded that emotional intelligence is directly proportional to the students mathematical critical thinking ability.Keywords: Emotional Intelligence, Mathematical Critical Thinking